2020
DOI: 10.1021/acsomega.0c00894
|View full text |Cite
|
Sign up to set email alerts
|

Ea22 Proteins from Lambda and Shiga Toxin-Producing Bacteriophages Balance Structural Diversity with Functional Similarity

Abstract: Enterohemorrhagic Escherichia coli (EHEC) outbreaks are commonly associated with contaminated food sources. Unlike normal intestinal bacteria, EHEC are lysogens of lambdoid bacteriophages that also carry a gene for Shiga toxin. Oxidative attack by the immune system or other stressors on the bacterial host can activate the lytic pathway of the latent phage genome to produce phage progeny and the release of Shiga toxin into the surrounding tissues. Within the genomes of bacteriophage λ and Shiga toxin-expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The ea22 gene provides some contrast to the three exo-xis genes that precede it. Not only is it the largest protein of the exo-xis region and multidomain in composition [ 52 ], but its function also favors lysogenic development over lytic development [ 27 ]. With this function in mind, Ea22 may serve as a new focal point for understanding how Stx + phage lytic program can be delayed during EHEC infections to limit the release of Shiga toxin.…”
Section: Structural Features Of the Conserved Exo-xis Region Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ea22 gene provides some contrast to the three exo-xis genes that precede it. Not only is it the largest protein of the exo-xis region and multidomain in composition [ 52 ], but its function also favors lysogenic development over lytic development [ 27 ]. With this function in mind, Ea22 may serve as a new focal point for understanding how Stx + phage lytic program can be delayed during EHEC infections to limit the release of Shiga toxin.…”
Section: Structural Features Of the Conserved Exo-xis Region Proteinsmentioning
confidence: 99%
“…From sequence comparisons and experimental evidence derived from deletion studies, and biophysical analysis of purified proteins and protein fragments, λ Ea22 may be considered in terms of a variable N -terminal region, a central tetrameric coiled-coil region, and a dimeric C-terminal region. The C-terminal region demonstrates the hallmarks of a domain since it can be separated from the protein by limited proteolysis treatment while still retaining exceptional thermostability [ 52 ]. As shown earlier in Figure 3 , a comparison of the AlphaFold and RoseTTAFold predictions for the λ Ea22 C-terminal domain as a monomer differ only in the positioning of the second helix with an overall backbone RMSD of 1.82 Å.…”
Section: Structural Features Of the Conserved Exo-xis Region Proteinsmentioning
confidence: 99%
“…The most variability among the Ea22 proteins occurs at the C-terminal region of the protein. In a few cases where purified proteins can be studied, the C-terminal region is dimeric like λ regardless of sequence, and the full-length protein is tetrameric suggesting there is evolutionary pressure to maintain a specific oligomeric state even when the sequence and structure are drifting 5 . It is possible, therefore, that Stx phages have acquired new domains that improve fitness while maintaining a similar architecture.…”
Section: Discussionmentioning
confidence: 99%
“…MurR is a putative transcription factor that could repress the murPQ operon, which is required for the cellular catabolism of the bacterial cell wall [ 55 ]. Also, Ea22, probably derived from bacteriophages, is an uncharacterized protein involved in the cell cycle control, cell division, and chromosome partitioning of E. coli [ 56 ]. Deletion-substitution mutagenesis has shown that Ea22 is responsible for the block to initiation of DNA replication [ 57 ].…”
Section: Discussionmentioning
confidence: 99%